Chemical Composition and Antibacterial Activity of the Essential Oil of Salvia macrochlamys Boiss. & Kotschy, from West Azarbayjan Province - Z Kazemizadeh; Z Habibi; M Yousefzadi; MA As,habi; M Heidari-Rikan (Institue of Medicinal Plants, ACECR, 2010)
Background: In the Flora Iranica this genus is represented by fifthy-eight species, seventheen of which are endemic. The genus Salvia are known for medicinal value, antibacterial and antioxidant properties. Objective: Investigation on essential oil of Salvia macrochlamys and antibacterial activity assessment. Methods: The aerial parts of S. macrochlamys were collected during the flowering stage from Marmishuo Hill in West-Azarbayjan Province, in July 2006 and were hydrodistilled for 3 hours, using a Clevenger-type apparatus to yield 0.35% (w/w) of yellowish oil and analyzed with GC and GC/MS. The constituents of the essential oil were identified by comparison of their mass spectra and retention indices (RI) with those given in the literature and authentic samples. Antibacterial activities of the essential oil were investigated according to the disc diffusion method and MIC value. Results: Thirty-four compounds were characterized in the essential oil of S. macrochlamys, representing 97.6% of the oil, of which β-Caryophyllene (32.7%), 1,8-Cineol (18.9%), were found to be the major components. The oil of S. macrochlamys showed high antibacterial activity against Bacillus subtilis, Staphylococcus aureus and Staphylococcus epidermidis. Conclusion: The oil of S. macrochlamys consists of monoterpen (44.4%) and sequiterpens (52.0%). The antibacterial avtivity can be attributed to 1,8-Cineol.